2013
DOI: 10.1038/npp.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol as a Mechanism for Sex Differences in the Development of an Addicted Phenotype following Extended Access Cocaine Self-Administration

Abstract: Women progress more rapidly after initial cocaine use to addiction as compared with men. Similarly, female rats appear to require less cocaine exposure before developing an addicted phenotype with evidence implicating estradiol as a potential mechanism. The goals of this study were to determine whether there are sex differences in the magnitude of the addicted phenotype under optimized conditions that induce its development in both males and females and to determine the role of estradiol in this effect. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 35 publications
8
85
0
1
Order By: Relevance
“…Psychostimulants. Ovariectomized female rats with extended access using a discrete trials procedure failed to show greater motivation to take cocaine after extended access, and this effect was reversed by estradiol (Ramôa et al, 2013). Estradiol facilitated responding in a discrete-trials procedure during escalation and the motivation to take cocaine during abstinence (Ramôa et al, 2013).…”
Section: Effects Of Hormones During the Reproductive Cycle In Femamentioning
confidence: 97%
See 1 more Smart Citation
“…Psychostimulants. Ovariectomized female rats with extended access using a discrete trials procedure failed to show greater motivation to take cocaine after extended access, and this effect was reversed by estradiol (Ramôa et al, 2013). Estradiol facilitated responding in a discrete-trials procedure during escalation and the motivation to take cocaine during abstinence (Ramôa et al, 2013).…”
Section: Effects Of Hormones During the Reproductive Cycle In Femamentioning
confidence: 97%
“…However, once females develop an "addicted" phenotype, their behavior looks very similar to that of males (Ramôa et al, 2013;Perry et al, 2015).…”
Section: Sex Differences In Drug Abusementioning
confidence: 99%
“…Recent studies of the relationship between hormones and cocaine found that estrogen plays an important role in the transition from recreational drug use to cocaine dependence (19). Specifically, using real-time exposures to drug cues and drug use, Kennedy and colleagues (2013) found that women were more sensitive than men to such exposures.…”
Section: Craving Stress and Hormonesmentioning
confidence: 99%
“…This is based on previous studies showing that OVX females display a reduction in cocaine IVSA that is normalized to intact female levels following E2 supplementation [19]. Also, another report revealed that OVX rats that received E2 supplementation displayed greater motivation to obtain cocaine relative to OVX rats that received vehicle [20]. …”
Section: Introductionmentioning
confidence: 97%